IDENTIFIKASI TELUR CACING Soil Transmitted Helminths (STH) PADA PENGRAJIN BATU BATA DI BANJAR PANDE DESA TULIKUP GIANYAR - Sri Ida Yani (Akademi Kesehatan John Paul II Pekanbaru, 2021)
Soil Transmitted Helminths (STH) are also called intestinal nematodes, which are often a problem for humans who are transmitted through soil. Workers in contact with the land are at risk of infection with Soil Transmitted Helmints (STH) eggs. Brick craftsmen who are accustomed to not wearing boots or footwear and gloves while working and lacking personal hygiene can be at risk of causing worm infections. Method used is descriptive with a sample of 30 people using the Direct Slide method. The results of research samples of brick craftsman faeces, it was found that 5 samples (16.7%) were positive for Soil Transmitted Helminths (STH) eggs with a prevalence of Ascaris lumbricoides (6.7%) and Hookworm (10%) and and 25 samples (83.3%) were negative for Soil Transmitted Helminths (STH) worm eggs. Discussion The employees who are directly in contact to the ground, especially brick craftsmen, have higher risk of being infected by worms due to lack of personal hygiene and not using Personal Protective Equipment (PPE) while working thus easier for the transmission of Soit Transmitted Helminths (STH) infection.